A Case Summary of Treatment for Frequent Bathroom Visits in Pediatric OCD. Issue 1 (2nd January 2020) - Cabeldue, Mollimichelle; McGlinchey, Eleanor
ABSTRACT: Pediatric obsessive-compulsive disorder is a common anxiety disorder impacting children and their families in several domains. This paper summarizes treatment of an elementary school-age child (i.e., Jane) diagnosed with OCD, characterized by frequent urges to use the bathroom, who also experienced additional stressors such as caregiver medical problems during treatment. Jane's symptom presentation initially confused her parents and other medical providers given its' manifestation as a physical problem. However, in the absence of any medical reason for her frequent urges to urinate, she was referred for psychological treatment. Exposure and response prevention was implemented and a consulting psychiatrist prescribed adjunctive medication. Aspects of the treatment and outcome measures are presented. During treatment, the family received psychoeducation about Jane's diagnosis and the nature of treatment, followed by implementation of exposure and response prevention. One major feature of treatment included multi-disciplinary collaboration, including collateral contact with her teacher and referral to a psychiatrist. After treatment, Jane and her parents reported no ongoing obsessions/compulsions. Additionally, she was able to re-join many activities she stopped participating in due to distress caused by OCD.